2021
DOI: 10.22159/ijap.2021v13i1.39742
|View full text |Cite
|
Sign up to set email alerts
|

Drug Release Control and Enhancement Using Carriers With Different Concentrations of Capmul® MCM C8

Abstract: Objective: The main aim of this study was to design a drug carrier capable to control and enhance the release of poorly water soluble drugs. Methods: Three polymeric formulations, based on poly (2-hydroxyethyl methacrylate) and loaded with different Capmul® MCM C8 concentrations (0, 10 and 20 % w/w), were prepared. Felodipine, which is a poorly soluble substance, was selected as a model drug. The effect of Capmul® MCM C8 on swelling behavior and in vitro release profile of the prepared polymer was invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…The used concentration of the bioavailability enhancer, capmul MCM C8, has significantly increased the release profile of the 5-amino salicylic acid, as demonstrated by D1, D2 and D7, D8 at each pH. This can be contributed to forming micelles within the polymeric matrix by the capmul ® MCM C8, thus enhancing the dissolution and release of the 5-amino salicylic acid [19]. The release profile of the model drug was also decreased significantly with an increasing concentration of the crosslinker (EGDMA), as demonstrated by F4, F5, and F6 at each pH.…”
Section: In Vitro Drug Release Studiesmentioning
confidence: 98%
See 1 more Smart Citation
“…The used concentration of the bioavailability enhancer, capmul MCM C8, has significantly increased the release profile of the 5-amino salicylic acid, as demonstrated by D1, D2 and D7, D8 at each pH. This can be contributed to forming micelles within the polymeric matrix by the capmul ® MCM C8, thus enhancing the dissolution and release of the 5-amino salicylic acid [19]. The release profile of the model drug was also decreased significantly with an increasing concentration of the crosslinker (EGDMA), as demonstrated by F4, F5, and F6 at each pH.…”
Section: In Vitro Drug Release Studiesmentioning
confidence: 98%
“…Shailendrakumar et al [18] employed a capmul ® MCM product with palm oil to improve the oral bioavailability of pentoxifylline. In another work, Bayan et al [19] reported the potential use of capmul MCM C8 to improve the dissolution of poorly soluble drugs. The produced polymeric formulations (Table 1) were loaded with 5-amino salicylic acid as a model dug, which is characterized by poor solubility/permeability and used as a firstchoice drug in the treatment of inflammatory bowel diseases that affect mainly the colon.…”
Section: Preparation Of Smart Polymeric Formulationsmentioning
confidence: 99%
“…Due to these classical treatment strategies, the patient immune system is damaged by the drugs, which leads to side effects. Recently, biomedical researchers have had a great interest in the uses of targeted drug delivery methods in cancer treatments [ 35 , 36 , 37 , 38 ]. Today, several synthetic drugs are available in the market for lung cancer cells targeting epidermal growth factor receptor (EGFR).…”
Section: Resultsmentioning
confidence: 99%
“…The size of the polymer also affects this behaviour, as it affects the surface area available for fluid penetration. The ability to control this behaviour encourages the use of polymers in many pharmaceutical drug delivery systems [1][2][3][4][5][6][7]. The pellets' swelling was examined in phosphate-buffered saline (PBS).…”
Section: Pellets' Swelling Assessmentmentioning
confidence: 99%
“…Targeted drug delivery to the colon has attracted the attention of many researchers owing to its tremendous advantages over systemic drug administration, including increased drug potency and efficacy and reduced adverse drug reactions [1,2]. Colonic drug delivery systems have been used to treat a plethora of bowel diseases encompassing colorectal carcinoma, ulcerative colitis, diverticulitis, Crohn's disease, and irritable bowel syndrome [3][4][5]. Colon-specific drug delivery has long been used to enhance therapeutic effectiveness by reducing unwanted absorption in other regions of the gastrointestinal tract, guaranteeing that the whole drug dose is specifically delivered to the site of interest in the colon [6,7].…”
Section: Introductionmentioning
confidence: 99%